Emotional management and stress : managing ambiguities - Styhre, Alexander; Ingelgård, Anders; Beausang, Peder; Castenfors, Mattias (Stockholm, 2003)
"Emotions and stress are inextricably entangled: being stressed has bodily as well as emotional implications for human beings. The widespread distinction between mind and body in organization theory, following the Cartesian doctrine, blocks the sufficient theoretization of stress. In general, there is a preference in organization theory toward linguistic, literary, and semiotic interpretations of organizational practices. Consequently, notions such as culture and discourse have been largely favoured. The limits of this tradition in Western thinking, Cartesian over Spinozist philosophy, are that mind is favoured over body, thinking over emotions, mind over matter. This paper presents a study of the experience of stress in a pharmaceutical company. It suggests that stress is to be conceived of as a bodily phenomenon while incorporating the emotional qualities of human beings. Being an outcome of a set of ambiguities, stress is produced in a social setting but has immediate bodily effects on employees."